(untitled) (Acta Scientiarum. Animal Sciences, 2026)
Postbiotics can play an essential role in feeding strategies that replace antimicrobial growth promoters and zinc oxide in diets for all phases of swine production. This study aimed to evaluate the impact of a yeast-based postbiotic on animal performance and pork meat quality. A total of 220 pigs (26.8 ± 0.1 kg of body weight and 68 days of age), the offspring of Camborough sows and PIC337 boars, were randomly assigned to four treatment groups in a 2 Ã— 2 factorial design with ten replications. The treatments resulted from the combination of sex (female or immunocastrated male) and dietary treatment (Control – basal diet, or Postbiotic – Saccharomyces cerevisiae fermentation product added at 0.5 kg per ton of feed). Each replication was a pen containing 11 animals. The trial lasted 101 days. Postbiotic supplementation did not affect animal performance (final body weight, average daily gain, and feed conversion ratio). However, regarding carcass traits, loin depth and lean meat were higher in the postbiotic treatment. Meat from the postbiotic treatment showed reduced lipid oxidation (TBARS), lower pH, and lower red intensity (a* parameter). In conclusion, adding yeast-based postbiotics to the feed of growing/finishing pigs does not affect performance, but it improves pork quality.